Gerakan Keagamaan dan Identitas Kultural Masjid Jendral Sudirman Yogyakarta - Fejrian Yazdajird Iwanebel (IBDA` : Jurnal Kajian Islam dan Budaya, 2019)
Abstract: The article aims at explaining the root and the form of religious based cultural movement initiated by Jendral Sudirman Mosque (MJS) Yogyakarta. The conundrum departs from the common assumption that mosque is usually regarded as the sacred place, not as profane as cultural performance. Since 2011, the MJS has carried out various cultural activism that is unique, paradox and distinct from the common mosques which activites are generally centered on religious piety. It is in this case that this paper discusses MJS from two aspects: the history of the MJS and its cultural strategy. In its history, the MJS underwent three phases of movement. At first, the mosque was subjugated by the militant Islamic movement which aims at establishing an Islamic state. The movement, then, shifted into an educational movement of the children. And later, it changed totally into religious cultural movement. At this regard, the cultural movement carried out by the MJS reflects an effort in shifting their old identity, while at the same time they are involved in a discursive approach to respond the contemporary challenge of Islamism.